Development of Formulation for Seasoning Banana Puree by Mixing with Tropical Fruits Paste Mixed with Banana Peel Powder and Passion Fruit Puree - Lichanporn, Intira; Nanthachai, Nanchanok; Tanganurat, Palida; Akkarakultron, Purin (Journal of Applied Research on Science and Technology (JARST), 2023)
This study aimed to develop a formulation for tropical fruit paste mixed with banana peel and passion fruit puree. Banana peel powder is fine-grained brown, and L* a* and b* were 38.38, -0.21, and 2.74%. Total soluble solids, pH, and titratable acidity were 3.16%, 6.50, and 10.73%, respectively. The total phenolic and antioxidant content of banana peel powder were 76.86 μg GAE/gDW and 45.47 μg Trolox/gDW, respectively. The effects of banana peel powder mixed with passion fruit puree on physical, chemical, and sensory qualities in banana paste were determined by using banana peel to passion fruit puree ratios of 0:0(control; BC), 150:0(B1), 100:50(B2), 50:100(B3), 0:150(B4), and 75:75(B5) g. The results showed that banana products used banana peel to passion fruit puree ratios of 50:100(B3), with the highest overall taste, color, and preference, equal to 8.52, 8.28, and 8.49 scores, respectively. The color (L*, a*, and b*) of banana products using banana peel to passion fruit puree ratios of 50:100 was 40.92, -1.01, and 2.09, respectively. It has a pH, titratable acidity, and total soluble solids of 5.22, 1.87%, and 23.27%. The phenolic content and antioxidant compounds were 7.70 μg GAE/gDW and 43.42 μg Trolox/gDW. The post-seasoning banana paste product contains phenolic compounds and antioxidants with 10.54 μg GAE/gDW and 43.04 μg Trolox/gDW. While paste banana products use banana peel to passion fruit puree ratios of 0:0(BC) and 0:100(B4), they have the lowest overall color, taste, texture, and acceptability scores. Therefore, adding banana peel powder and passion fruit puree to banana paste products can help increase antioxidants.